Understanding the Potential of Variable Tolling to Smooth Congestion on Downstream Facilities: Applications of a Joint Time-of-Day and Route Choice Model. Issue 1 (2016) - Erhardt, Gregory D.; Patil, Sunil; Light, Thomas; Tsang, Flavia; Burge, Peter; Sorensen, Paul; Zmud, Mia
The aim of this research was to understand the conditions under which time-varying tolls could be used to effectively smooth congestion on a downstream, untolled roadway. This question was answered in the context of the 183A Turnpike in Texas, but the analysis was extended to draw lessons for the potential use and evaluation of time-varying tolls as a congestion management strategy elsewhere. The study relied on two primary data sources: license plate reader data, to observe traffic routing, and a stated preference survey, to understand travelers' trade-offs between travel time, tolls, and time-of-day shifts. A joint time-of-day and route choice model was developed and implemented in a spreadsheet for the rapid evaluation of a range of scenarios. Model inputs were then varied across key dimensions to achieve a better understanding of the conditions under which such a strategy might or might not be effective. The analysis revealed that under the conditions and constraints specific to the 183A corridor, time-of-day tolling would have a limited effect, but that there are a range of conditions for which time-of-day tolling could be a cost-effective means of managing downstream congestion.